DEVELOPING A REGISTER OF OUTCOMES OF CHRONIC CORONARY HEART DISEASE: CHD PROGNOSIS STUDY - S. N. Tolpygina; S. Yu. Martsevich; E. A. Gofman; A. M. Malysheva; Yu. N. Polyanskaya; A. D. Deev (Кардиоваскулярная терапия и профилактика)
Aim. Using the data from the CHD PROGNOSIS register, to assess the long-term survival of patients with stable coronary heart disease (CHD) confirmed by a diagnostic coronary angiography (CAG).Material and methods. The study design (retro- and prospective observational cohort study) agreed with the register principles. The study included all consecutive patients (Moscow Region residents) who were hospitalised to the State Research Centre for Preventive Medicine with a preliminary diagnosis of CHD, for a diagnostic CAG and therapeutic strategy selection (01.01.2004–31.12.2007). The total number of participants was 641 (500 men and 141 women). Vital status was ascertained in 551 patients (86%). Mean follow-up time was 3,8 years (range 0,76–6,52 years).Results. The register participants had a high prevalence of conventional risk factors and adverse clinical and anamnestic characteristics. CAGconfirmed coronary artery (CA) stenosis ≥50% was registered in 563 patients. In 24 out of 78 individuals with “intact” CA, coronary syndrome X or vasospastic angina was diagnosed; in the other 54, CHD diagnosis could not be confirmed. During the hospitalisation, balloon angioplasty was performed in 38% of the patients with known vital status. Before hospitalisation, the main drug classes with proven prognostic benefits were administered insufficiently often. During the follow-up period (mean follow-up 3,9 years), 50 patients died. All-cause mortality was 11,38±1,61 per 1000 person-years. The leading cause of death was chronic CHD (84%), which confirms high levels of cardiovascular risk in these patients. In total, fatal and non-fatal complications, including revascularisation episodes, were registered in 36%.Conclusion. The established register of stable CHD includes a typical cohort of chronic CHD patients who are referred for invasive diagnostics and treatment. Therefore, the register is expected to provide valid information on the factors determining prognosis and effectiveness of medical intervention, such as pharmacological therapy and percutaneous revascularisation.